Ras Pathways on Prox1 and Lymphangiogenesis: Insights for Therapeutics - Bui, Khoa; Hong, Young-Kwon (Frontiers in Cardiovascular Medicine, 2020)
Over the past couple of decades, lymphatics research has accelerated and gained a much-needed recognition in pathophysiology. As the lymphatic system plays heavy roles in interstitial fluid drainage, immune surveillance and lipid absorption, the ablation or excessive growth of this vasculature could be associated with many complications, from lymphedema to metastasis. Despite their growing importance in cancer, few anti-lymphangiogenic therapies exist today, as they have yet to pass phase 3 clinical trials and acquire FDA approval. As such, many studies are being done to better define the signaling pathways that govern lymphangiogenesis, in hopes of developing new therapeutic approaches to inhibit or stimulate this process. This review will cover our current understanding of the Ras signaling pathways and their interactions with Prox1, the master transcriptional switch involved in specifying lymphatic endothelial cell fate and lymphangiogenesis, in hopes of providing insights to lymphangiogenesis-based therapies.